Linggarjati Agreement as A Diplomatic Effort In An Effort to Maintain Indonesian Independence - Yuniarto, Bambang; Kusumawardhan, Tiara Adiyanti; Nurfadlilah, Fatkhurezky; Fahrezi, Fahmi; Wahyuni, Wahyuni (Sahabat Publikasi, 2023)
Independence is a right for every nation, this is in accordance with what is contained in the preamble to the Constitution of the Indonesian state. And the independence that has been obtained must be fought for sovereignty so that the country is recognized de facto by other countries. To maintain this sovereignty can use by means of diplomacy, which is a way of settlement by means of negotiations to settle even between two countries. This is also done by the Indonesian state to maintain its independence, namely in the Linggadjati agreement. In writing this research we aim to explore further about the events of the environmental negotiations, and the focus of our research is the historical side that occurred in the environmental agreement. The research method we use is the historical method where this historical method aims to ascertain and retell facts that occurred in the past.